Women Entrepreneurs in the Beauty Industry: Is it Sustainable? - Chitra, M.; Kalpana, B. (Indian Journal of Finance, 2014)
Thousands of beauty care service providers have sprung up all over the country in the last decade as the significance of being and looking beautiful is increasing. Though there are a plethora of studies on women entrepreneurship, studies related to women in the beauty industry are not common, and there are hardly any studies that have examined the sustainability of beauty salons run by women entrepreneurs. The present research study was conducted to bridge the gap by suggesting a sustainable model for the beauty salon industry with the objectives to identify the factors that motivated women entrepreneurs to start their beauty salons, to know the reasons for selecting a particular location for opening a beauty salon, to identify the inter - relationship between elements of the business model and sustainability of beauty salons, and to present a sustainable business model. Data were collected from 350 women entrepreneurs in Chennai during October to December 2013 by using the questionnaire method and by adopting the simple random sampling technique. Frequency and percentage analysis were carried out to study the socio-demographic features of the respondents, and factor analysis was used to identify the factors affecting the motivation levels of the respondents. To discriminate the area of operation of beauty salons based on motivational dimensions, discriminant analysis had been employed. Path analysis was employed to study the inter-relationship between the elements of the business model and to ascertain the sustainability of the beauty salon business.